INCLUSIVE TEACHING PRACTICES: CHALLENGES AND POSSIBILITIES FOR ACHIEVING EDUCATION FOR ALL - Vaillant, Rosângela Gomes; Austríaco-Teixeira, Phelipe; da Silva, Ana Maria Cunha; Morais, Ana Célia Santana; dos Santos, Thais Albertina Pereira; Costa, Rogers Paul da Silva; Nogueira, Telmo Rosa; dos Santos, Stephanie Cunha Araujo (Seven Editora, 2025)
Inclusive education constitutes a fundamental right that aims to guarantee full access to knowledge for all individuals, regardless of their physical, cognitive, or sensory characteristics. This study analyzes inclusive teaching practices implemented in Brazilian schools, identifying the main challenges faced by educators and the concrete possibilities for achieving accessible education for all. The research is characterized as qualitative, applied in nature, and with descriptive and analytical objectives, adopting systematic literature review as a technical procedure complemented by documentary analysis of educational public policies. Data collection includes Brazilian publications conducted between 2021 and 2024, selected from national and international scientific databases. The results show that inclusive education faces multidimensional challenges related to structural inadequacy, insufficient material and human resources, gaps in teacher training, and persistence of attitudinal barriers. Simultaneously, concrete possibilities for inclusion are identified through the use of assistive technologies, differentiated methodologies, and continuing education programs. It is concluded that the implementation of inclusive education requires articulated investments in infrastructure, professional training, pedagogical resources, and cultural transformation of educational institutions, representing an essential ethical and political commitment for building democratic and equitable societies.DOI: https://doi.org/10.56238/sevened2025.038-040